Integration of complementary and alternative medicine into family practices in Germany: results of a national survey - Joos, Stefanie; Musselmann, Berthold; Szecsenyi, Joachim (Evidence-based complementary and alternative medicine, 2011)
More than two-thirds of patients in Germany use complementary and alternative medicine (CAM) provided either by physicians or non-medical practitioners (“Heilpraktiker”). There is little information about the number of family physicians (FPs) providing CAM. Given the widespread public interest in the use of CAM, this study aimed to ascertain the use of and attitude toward CAM among FPs in Germany. A postal questionnaire developed based on qualitatively derived data was sent to 3000 randomly selected FPs in Germany. A reminder letter including a postcard (containing a single question about CAM use in practice and reasons for non-particpation in the survey) was sent to all FPs who had not returned the questionnaire. Of the 3000 FPs, 1027 (34%) returned the questionnaire and 444 (15%) returned the postcard. Altogether, 886 of the 1471 responding FPs (60%) reported using CAM in their practice. A positive attitude toward CAM was indicated by 503 FPs (55%), a rather negative attitude by 127 FPs (14%). Chirotherapy, relaxation and neural therapy were rated as most beneficial CAM therapies by FPs, whereas neural therapy, phytotherapy and acupuncture were the most commonly used therapies in German family practices. This survey clearly demonstrates that CAM is highly valued by many FPs and is already making a substantial contribution to first-contact primary care in Germany. Therefore, education and research about CAM should be increased. Furthermore, with the provision of CAM by FPs, the role of non-medical CAM practitioners within the German healthcare system is to be questioned.